Nomenclatural issues in Rhagovelia Mayr (Hemiptera: Heteroptera: Gerromorpha: Veliidae) - Nemésio, Andrés; Melo, Alan L. (Zootaxa, 2012)
Nieser & Polhemus (1999) described four species of Rhagovelia (Hemiptera: Heteroptera: Gerromorpha: Veliidae) from the state of Minas Gerais, southeastern Brazil: Rhagovelia ochroischion, R. sbolos, R. trianguloides, and R. turmalis. Nevertheless, these same nomina were used in an identification key by Nieser & Melo (1997).